Pendampingan Pembuatan Jamu Instan Tanaman sebagai Produk KB Alami pada Ibu Pkk - Marwati, Marwati; Khairi, Nur; Alexandra, Francisca Diana; Fadillah, Nurul; Anggyasti, Anggyasti (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: The purpose of community service is to increase the knowledge of the PKK cadre women on the types of medicinal plants that are efficacious as natural birth control, increase their knowledge of traditional medicine processing that is efficacious as natural family planning, and increase their knowledge of reproductive health and types of family planning. Methodology: This study was conducted at the Moreira Farm in the Al Anshar East Timor Islamic Boarding School area. Hydroponics innovation has been applied by increasing the quantity and quality of hydroponics through technological tools and innovations to streamline and increase the yield of hydroponic plants to achieve higher quality than before. Results: The service method applied is the method of applying innovations by providing counselling assistance and practicing making instant herbal medicine Natural contraception of traditional medicine to increase understanding to cadres of PKK mothers in the development of natural materials. Conclusion: The conclusion of this activity is the increased knowledge of PKK women cadres and the community about the utilization of traditional medicine as instant herbal medicine for natural contraception to reduce the birth rate. Limitation: The knowledge of the PKK cadre and the community on the use of traditional medicine for natural family planning is still lacking. Contribution: This service is useful in the traditional medicine industry and the development of natural materials as products.